Transfusion Reactions in Pediatric Patients: An Analysis of 5 Years of Hemovigilance Data From a National Center for Children's Health in China - Guo, Kai; Wang, Xiaohuan; Zhang, Huimin; Wang, Mengjian; Song, Shanshan; Ma, Shuxuan (Frontiers in Pediatrics, 2021)
Objective: This study aimed to describe transfusion reactions of pediatric patients from a National Center for Children's Health in China and to examine reaction incidents, reaction types by blood transfusion, and the associated blood products resulting in transfusion reactions. Methods: We compared transfusion reaction rates, among platelets, plasma, and red blood cells (RBCs) using a retrospective analysis of pediatric patients treated with blood transfusion based on data from the National Center for Children's Health (Beijing, China) by a hemovigilance reporting system from January 2015 to December 2019. Results: Over the past 5 years, 165 reactions were reported, and the overall incidence was 1.35‰ (95% CI: 1.14–1.55‰; 165/122,652); for each separate year, the incidences were 1.25‰ (95% CI: 0.76–1.74‰; 25/20,035; 2015), 1.09‰ (95% CI: 0.65–1.52‰; 24/22,084; 2016), 1.66‰ (95% CI: 1.14–2.18‰; 39/23,483; 2017), 1.36‰ (95% CI: 0.92–1.81‰; 36/26,440; 2018) and 1.34‰ (95% CI: 0.93–1.75‰; 41/30,610; 2019). Transfusion reaction incidents by person included 0.37‰ (95% CI: 0.21–0.53‰; 21/56,815) RBCs, 2.98‰ (95% CI: 2.33–3.64‰; 79/26,496) platelets and 1.65‰ (95% CI: 1.25–2.05‰; 65/39,341) frozen plasma. According to the analysis by blood products, the incidence of transfusion was 0.34‰ (95% CI: 0.20–0.48‰; 23/66,958) for RBCs, 3.21‰ (95% CI: 2.50–3.92‰; 78/24,318.5) for platelets, and 0.94‰ (95% CI: 0.71–1.17‰; 64/67,912) for frozen plasma. Transfusion reactions were most commonly associated with platelets, followed by plasma and RBC transfusions. The types of blood transfusion reactions were mainly allergic reactions (86.67%) and febrile non-hemolytic transfusion reactions (FNHTRs, 4.24%). The disease types of pediatric patients with transfusion reactions were concentrated among those with blood system diseases. A total of 80.61% of children with transfusion reactions had a previous blood transfusion history. Conclusions: Transfusion reactions are still relatively common in pediatric patients, and additional studies are necessary to address the differences in reaction rates, especially allergic and FNHTRs. Robust hemovigilance systems do include a special section dedicated to children will further the understanding of these reactions and trends, and prospective randomized clinical controlled trials may need to be conducted to perform preventive and corrective measures.